Memorie di guerra. Verso la riapertura del Bunker della Prefettura e della Torre delle Sirene di Milano - Breda, Maria Antonietta; Fianchini, Maria (Scienze del Territorio, 2017)
The paper concerns the project, promoted by Metropolitan city and Polytechnic university of Milan, of returning to public use Torre delle Sirene – seat of the Milan air-raid alert control unit – and Bunker della Prefettura. Two buildings connected to each other and very significant as memories of the Second World War and, most of all, of the ordinary life of civilian people under siege, a condition still regarding so many people around the world at present. Both the buildings have been neglected and deteriorated since a few years, but they still preserve traces of the past use. The reopening project is difficult due both to the typological and location characters of the buildings and to the lack of available financial resources. The objective of the project is to transform the former central point of the air-raid defence system into the epicentre of a new collective alert system on the topic of war, operating through memories of the past. Moreover, this could become the centre of a wider and widespread heritage system of local air-raid shelters: a network of material and immaterial goods organized by the common logic of enhancing memory, in order to strengthen the culture of peace and realize in the city a cultural itinerary based on historical values.